2011
DOI: 10.1038/aja.2010.180
|View full text |Cite
|
Sign up to set email alerts
|

PSA-based prostate cancer screening: the role of active surveillance and informed and shared decision making

Abstract: Since the first publication describing the identification of prostate-specific antigen (PSA) in the 1960s, much progress has been made. The PSA test changed from being initially a monitoring tool to being also used as a diagnostic tool. Over time, the test has been heavily debated due to its lack of sensitivity and specificity. However, up to now the PSA test is still the only biomarker for the detection and monitoring of prostate cancer. PSA-based screening for prostate cancer is associated with a high propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The Gleason grade, PSA, and clinical stage are the most widely used pretreatment prognostic parameters for PCa patients. However, the prognosis of PCa patients is limited due to the limitation of these prognostic biomarkers [8, 23, 24]. Emerging studies have started to identify novel biomarkers for PCa and have found that noncoding RNAs are associated with PCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…The Gleason grade, PSA, and clinical stage are the most widely used pretreatment prognostic parameters for PCa patients. However, the prognosis of PCa patients is limited due to the limitation of these prognostic biomarkers [8, 23, 24]. Emerging studies have started to identify novel biomarkers for PCa and have found that noncoding RNAs are associated with PCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, as has been reported, tests have been performed without adequately informing patients about advantages, and disadvantages of PSA measurement. [2][3][4] Nowadays, guidelines of American Urological Association, American Cancer Society, and United States Preventive Services Task Force require mutual decision between the physician, and the patients about performing PSA test. [5] Upper limit of normal (ULN) for prostatespecific antigen was recommended as 4 ng/ mL when it was firstly introduced into clinical practice.…”
mentioning
confidence: 99%
“…[1] US Food and Drug Association (FDA) approved PSA as an auxillary diagnostic test in the management of the patients diagnosed as prostate cancer (PCa). [2] It was introduced into clinical practice in 1987 as a diagnostic marker. [3] Catalona 1991 recommended use of PSA as a screening test for PCa.…”
mentioning
confidence: 99%
“…Conventionally, prostate cancer is detected by digital rectal examination, histopathological analysis, and prostate specific antigen (PSA) assays [38,39]. However, these techniques have limitations, and new molecular biomarkers are being characterized that potentially help in detecting the disease, risk assessment, and follow-up of treatment and survival [40].…”
Section: Biomarkers Of Prostate Cancer Detection Progression Risk Amentioning
confidence: 99%